Electronic Government Rukun Tetangga Model - Darius Antoni; Muhamad Akbar; Fatoni Fatoni (Jurnal Sistem Informasi, 2018)
E-government is the one of facilities of government to interact and communicate with the citizen as the government's ability to improve service performance. However, not all citizen, including the poor, can benefit the e-government services. To answer the issue, this research developed e-government model of Rukun Tetangga (RT) based on eight factors consisting of Content providers, Direct-to-consumer, Value-net-Integrations, Full-service providers, Infrastructure service providers, Market, Collaboration and Virtual Communities. Quantitative research was used to collect data through interview with 24 participants including Head of RT, Citizen and Employees District Office in Palembang. The findings of this study showed that an e-government RT model was required to help Palembang Government to meet needs of the citizen, which had impacts to improve services to entire levels of society.